The great archaeologists - Fagan, Brian M. (Thames & Hudson, 2014)
Organized into six thematic sections, this book gives short, vivid biographies and fresh assessments of the achievements of 70 of the worlds greatest practitioners, written by a 40-strong team of contributors, themselves all eminent archaeologists and authors. All these archaeologists very different individuals, and often in deep disagreement with one another have established the subject as a scientific discipline and vastly broadened and deepened our knowledge of the human past. Authoritative and entertaining, this is a book for anyone fascinated by the human past and its discovery
Keywords: Aufsatzsammlung; Biografie; Archäologin; Archäologe